First report on the synthesis and structural studies of trans-Phakellistatin 18: a rotamer of marine natural product phakellistatin 18. Issue 9 (3rd May 2023) - Kanwal, Iqra; Mushtaq, Farkhanda; Ali, Hunain; Tufail, Priya; Jahan, Humera; Shaheen, Farzana
Abstract: Phakellistatin peptides from marine organisms are the sources of proline-rich cyclic peptides with reported significant antitumor activities. Phakellistatin 18 (1 ), reported from marine sponge Phakellia fusca, contains three proline-peptide linkages in cis form. We attempted the total synthesis of natural product 1 through solution-phase macrocyclization approach, as a result, the synthetic cyclic peptide 2 was obtained as a rotamer of natural product having all three proline residues in trans -conformation. Here, we describe the synthesis, structural, and cytotoxicity studies of trans -Phakellistatin 18 (2 ), and its analog [Ala 1, 3, 6 ]-Phakellistatin 18 (3 ). Detailed NMR studies were carried out to characterize the synthesized peptides, and anti-cancer screening was performed by using MTT assay. The synthetic trans -Phakellistatin 18 (2 ) (IC50 =67.5 ± 2.938 µM) showed comparable cytotoxicity against HepG2 cancer cell line with standard drug doxorubicin (IC50 =63.88 ± 6.48 µM). Here, the first synthetic and structural studies on trans -Phakellistatin 18 (2 ), and its anticancer screening against HepG2 cell line was reported. Graphical Abstract: UF0001